Análise da poluição eletromagnética na região urbana de Mossoró-RN - Santana, Talles Amony Alves de (Universidade Federal Rural do Semi-Árido, 2018)
The fast human progress and a constant technological innovation in the area of telecommunications makes more and more people exposed to the electromagnetic radiation of the most varied natures. The concern with the possible health risks that this exposure can cause in the population causes that several regulatory agencies develop studies with the objective of establishing acceptable limits of human exposure to this type of radiation. Knowledge of these levels of radiation exposure and how electromagnetic fields are distributed spatially in a particular region is of paramount importance for the development of protection techniques that are effective against exposure to radiation reducing the risks to people in these areas. This work aims to study the distribution of electromagnetic radiation in the urban region of Mossoró by measuring the intensity of electric fields, magnetic fields and power density in 200 points using a suitable meter in the 10 MHz to 8 GHz range, based on the methodology proposed in Resolution 303 of ANATEL. And with these data, determine, through the use of statistical parameters, the most appropriate interpolation technique to estimate the spatial distribution of these fields in non-sampled areas using contour maps, created by the Golden Surfer® software, responsible for indicating the places most exposed to electromagnetic radiation. The measurement points were chosen based on the medium distance between the radio base stations in each of analysis zones. The measured values were compared with those established by regulatory organizations to be analyzed according to established standards
Keywords: Radiação; Poluição eletromagnética; Técnicas de interpolação; Radiation; Electromagnetic pollution; Interpolation techniques; ENGENHARIAS::ENGENHARIA ELETRICA